Fostering Creativity among Young Children - Yadav, Padma; Prasad, Jyoti Kant (THE PRIMARY TEACHER, 2012)
The nursery school located in IIT campus, Hauz Khas, New Delhi is an experimental model school of NCERT. It has two year’s ECCE programme wherein children between 3-5 years are enrolled and have ample opportunities for play and learn. Activities are conducted in all the aspects of child development. Creative expression and aesthetic appreciation are given due importance. Children’s creative work is frequently misunderstood. At the foundation stage where opportunities to draw freely is frequently available to children, more stress is given by the parents and the teachers on copying from the board or making of correct shape or writing work rather than communication and creativity. Drawings are one of the many languages children use to express themselves